A Creative Approach to Teaching Geometry in the Primary Grades - Toshpulatova Niyokhon Shavkatjonovna (International Journal on Orange Technologies, 2021)
This article is about "Creative Approaches to Teaching Geometry in the Primary School." Geometric material plays an important role in elementary mathematics. The main purpose of the study of geometric material is to learn about geometric figures (point, straight and curved line, straight line cross section, broken line, polygon, circle and circle) about their elements, between figures and their elements is to compile a complete system of perceptions about relationships, some of their properties.